Possums-based parental education for infant sleep: cued care resulting in sustained breastfeeding - BORAN, PERRAN (SPRINGER, 2021)
For infants and their families, sleep consolidation is important in maturing neural and circadian rhythms, and in family dynamics. The Possums Infant Sleep Program is a cued care approach to infant sleep, responding to infant cues in a flexible manner, dialing down the infant's sympathetic nervous system. The current study evaluated the effect of the Possums program on infant sleep and breastfeeding in infants (6-12 months) from a well-child outpatient clinic in Turkey, with the program intervention group (n = 91) compared with usual care (n = 92). In total, 157 mother-infant dyads completed the study. Infant sleep and breastfeeding rates were assessed at baseline and after 3 months. Nocturnal wakefulness, daytime sleep duration, naps, and night wakening decreased in both groups. Nocturnal sleep duration and the longest stretch of time the child was asleep during the night increased significantly in both groups without any change in total sleep duration. Night wakening was significantly lower and nocturnal sleep duration was significantly higher in the intervention group. However, mixed effects model analyses indicated no significant differences between the groups on any of the sleep outcomes after adjusting for confounders. Despite this, breastfeeding rates were significantly higher in the intervention group compared with those in the usual care group at follow-up. Conclusion: The Possum infant sleep program provided equivalent positive results on sleep parameters compared to usual care while advocating a more cued response. The critical difference was evident in sustained breastfeeding.
Keywords: Infant; Breastfeeding; Parents; Sleep; Wakefulness